Induksi dan Regenerasi Kalus Jagung yang Ditransformasi dengan Gen CsNitr1-L melalui Penembakan Partikel - A. Dinar Ambarwati; Edy Listanto; Slamet Slamet; Umar Umar; Sustiprijatno Sustiprijatno; Sutoro Sutoro (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2015)
The success in development of transgenic plants is influenced by the regeneration system. The objective of the study was toassess the response of maize genotypes to regeneration system of organogenesis and embryogenesis, after transformed withCsNitr1-L gene through particle bombardment. Induction and callus regeneration of maize immature embryos of inbred linesUlt:cm.1#, ARC 178-123-112-XB3, and AZ2 were conducted through organogenesis, whereas those inbred lines AZ1, AZ2,P4G19(S)C2.59.3.3.1.3 and P4S3.29.4.4.1 were conducted through embryogenesis somatic. Transformation of CsNitr1-L gene wasdone with the distance of bombardment of 7 cm and 9 cm and calli were then selected using 10 mg/l hygromycin. All explants(100%) of inbred lines Ult:cm.1# formed organogenic callus, while callus formation of ARC 178-123-112-XB3 was 94.3% and AZ2was 60.5%. Ult:cm.1# was the most responsive line to the regeneration of organogenesis and produced 24 green shoots,compared with ARC 178-123-112-XB3 which produced one green shoot and AZ2 that did not produce green shoots. The highestpercentage of embryogenic calli formed through somatic embryogenesis was obtained on inbred lines AZ1 (85.4%) and thelowest was on P4S3.29.4.4.1 (18.9%). Inbred lines AZ1 had the highest percentage of regeneration (50.7%) and produced 62plants, followed by P4G19(S)C2.59.3.3.1.3 that produced 17 plants (2.8%) and P4S3.29.4.4.1 which produced two plants.Preliminary identification on 31 putative transgenic plants through PCR analysis produced 22 plants (70.96%) that contained nptIIgene.